2016
DOI: 10.1111/jerd.12239
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Accelerated Aging on the Color Stability of Dental Zirconia

Abstract: After prolonged aging, discrete color changes can occur in zirconia, particularly when it is contact with the oral environment, as is the case of abutments and monolithic crowns. Thus, clinical and laboratory care should be taken to maintain surface integrity of zirconia, minimizing aging. (J Esthet Restor Dent 28:304-312, 2016).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…The monolithic zirconia, without an overlaying ceramic veneer, is directly exposed to the water and body fluids. The water exposure at 37 °C leads to low-temperature degradation (LTD) by phase transformation from a tetragonal to a monoclinic structure [32,33]. Phase transformation to monoclinic led to a 4% increase in volume; consequently results in structural disintegration, surface roughness and the development of micro-cracks [34].…”
Section: Discussionmentioning
confidence: 99%
“…The monolithic zirconia, without an overlaying ceramic veneer, is directly exposed to the water and body fluids. The water exposure at 37 °C leads to low-temperature degradation (LTD) by phase transformation from a tetragonal to a monoclinic structure [32,33]. Phase transformation to monoclinic led to a 4% increase in volume; consequently results in structural disintegration, surface roughness and the development of micro-cracks [34].…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining the optical properties of an esthetic restoration for a long‐time of its usage is also essential for its clinical success. It has been reported that after aging, discrete color changes can occur in resin, ceramic, or zirconia, particularly when it is contact with the oral environment …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have searched the color stability of CAD‐CAM materials and reported that polymer composites undergo clinically perceptible color change in staining solutions. Unlike glass ceramics, ceramic‐polymer materials contain a polymer component, exhibited higher color change in staining solution than lithium disilicate .…”
Section: Discussionmentioning
confidence: 99%
“…Achieving optimal esthetic outcomes with zirconia‐based restorations is still challenging due to multiple factors that affect the final color, such as fabrication techniques or aging . Recent studies have reported that zirconia submitted to accelerated aging also showed optical differences …”
Section: Introductionmentioning
confidence: 99%